2016
DOI: 10.4172/2167-0420.1000342
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Desired Family Size among Residents of Assela Town

Abstract: Background: Ethiopia, like most Countries in Sub-Saharan Africa, is experiencing rapid population growth. The rapid growth prevents national development effort and affects maternal and child health. Different factors influence family size at different levels in different Societies. This Study assessed factors affecting family size preferences in Assela town where data was not available in this regard. Objective:To determine desired family size and identify factors influencing family size among residents of Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Progressive research has provided the opportunity to cost effective health check-up in every possible corner of the globe. 'Journal of Women Health Care' is among such journals which are devoted to gather information about women health, which could provide a better world for women [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Progressive research has provided the opportunity to cost effective health check-up in every possible corner of the globe. 'Journal of Women Health Care' is among such journals which are devoted to gather information about women health, which could provide a better world for women [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have also explored the influencing behavior of children in single-parent families and found children to exert higher influence in single-parent families than those from two-parent families (Anderson et al, 1989). Contrary to this, some researchers have also found that teenagers from single-parent families are not more likely to be more influential than their counterparts in two-parent families (Dibaba and Mitike, 2016;Chaudhary, 2015;Lachance et al, 2000). India is a country known for its cultural diversity.…”
Section: Children As Influencersmentioning
confidence: 99%
“…Previous studies conceded the effect of family size (in terms of the number of siblings) on the influence exerted by children in family buying decisions. Some studies have found children's influence to increase in large families (Dibaba and Mitike, 2016;Ali et al, 2013;Jenkins, 1979), while others have found that children in large families perceived significantly less influence than children in small families (Page et al, 2017;Guneri et al, 2009), and some of the studies have found that the size of the family does not affect children's influence attempts (Akinyele, 2010). Smaller families when compared with large families can provide better education and more material wealth to their children and hence, more opportunities for a child to actively participate in family buying decisions, which may be Family consumption decisions easier if he/she is not competing with other children in the family (Johnson et al, 1994).…”
Section: Children As Influencersmentioning
confidence: 99%
“…The less educated are discouraged or opposed to such use. Moreover, women who attained a secondary and higher level of education are found to be 2 and 2.6 times more likely to prefer a small family size compared to women who had no education (Dibaba & Mitike, 2016). Occupation is used to relate to the lucrative pursuits which the respondents implied to generate income.…”
Section: Literaturementioning
confidence: 99%
“…This study is also directed only at two religious communities, which gives a more limited result. Besides, most of the works were accomplished by African researchers (Caldwell, 1980;OIOMU, 2000;Dibaba & Mitike, 2016).…”
Section: Research Gapmentioning
confidence: 99%